FILM AS AN EDUCATIONAL MEDIA IN BUILDING AWARENESS ON WILD ANIMAL CONSERVATION (CASE STUDY: PETUALANGAN SHERINA 2) - Setiaji, Gumelar; Altamira, Melisa Bunga (Jurnal Vokasi Indonesia, 2024)
Currently, films are not only a medium for entertainment, but can also be used as a medium for information, persuasion, and even education. Nature conservation is one of the environmental issues that is currently of concern. In a survey conducted by a non-governmental organization, the public paid sufficient attention to protecting biodiversity, flora, and fauna. Wild animal conservation is an issue that will be addressed in this research. The film "Petualangan Sherina 2" is a musical genre film that focuses on the importance of the conservation of wild animals, namely orangutans. This research will discuss how a film can be used as a communication medium to educate the public in building awareness of wild animal conservation. Through descriptive qualitative research with literature studies, it is hoped that this research can provide an overview of films that can be used as educational media. The research results show that films can be used as educational media to increase awareness of wild animal conservation. The expected action is a change in mindset and community participation in the sustainability of wild animal conservation. Keywords: Films, Educational Media, Awareness, Wild animal conservation